1984
DOI: 10.2170/jjphysiol.34.19
|View full text |Cite
|
Sign up to set email alerts
|

Operation of internal Na-dependent Ca influx mechanism associated with catecholamine secretion in the adrenal chromaffin cells.

Abstract: The cat adrenal gland was retrogradely perfused with a medium lacking divalent cation, and the secretion of catecholamines was induced by Ca reintroduction with or without simultaneous removal of external Na. These responses were markedly reduced after prior exposure to a medium containing Mg (1 mM) or lacking Na. The inhibition caused by Mg was reversed by ouabain treatment. Reversing the concentration gradient for Na alone by replacing external Na with Tris, choline, or Li did not stimulate catecholamine sec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

6
18
0

Year Published

1985
1985
2004
2004

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(24 citation statements)
references
References 34 publications
(42 reference statements)
6
18
0
Order By: Relevance
“…On the other hand, the responses to histamine (0.5 mM) or Ca (0.5 mM) reintroduction during exposure to a medium lacking divalent cation (DOUGLAS and RUBIN, 1963;SORIMACHI and NISHIMURA, 1984) were little affected by TPA (55±11 % in case of histamine, N=3, and 52±17% of the preceding controls in case of Ca reintroduction, N= 3). These results raise the possibility that TPA somehow activates voltage-dependent Ca channels as does dihydropyridine BAY-K-8644 (GARCIA et al, 1984).…”
mentioning
confidence: 88%
“…On the other hand, the responses to histamine (0.5 mM) or Ca (0.5 mM) reintroduction during exposure to a medium lacking divalent cation (DOUGLAS and RUBIN, 1963;SORIMACHI and NISHIMURA, 1984) were little affected by TPA (55±11 % in case of histamine, N=3, and 52±17% of the preceding controls in case of Ca reintroduction, N= 3). These results raise the possibility that TPA somehow activates voltage-dependent Ca channels as does dihydropyridine BAY-K-8644 (GARCIA et al, 1984).…”
mentioning
confidence: 88%
“…Previous results have indicated that the inhibition of Na pump overcame the inhibitory effect of Mg treatment, so that Ca re-introduction caused substantial secretion. This restored response was believed to be due to activation of Ca influx mechanism linked with Na efflux because of the increase in the concentration of internal Na (ESQUERRO et al, 1980;GARCIA et a!.,1981;SORIMACHI and YAMAGAMI, 1983;SORIMACHI and NISHIMURA, 1984). To see whether or not Bay-K-8644 potentiates the secretion due to this Ca influx mechanism, we investigated the effect of this agent on the response to Ca re-introduction under conditions in which Na pumping activity was inhibited by K deprivation, ouabain, or a metabolic inhibitor (KCN).…”
Section: Bay-k-8644mentioning
confidence: 99%
“…These results led to the proposal that secretion was induced by Ca influx linked with Na efflux (ESQUERRO et al, 1980;GARCIA et al, 1980GARCIA et al, , 1981SORIMACHI et al, 1981;SORIMACHI and NISHIMURA, 1984). On the other hand, this response is abolished by organic (methoxy-verapamil and nifedipine;AGUIRRE et a!., 1979;NISHIMURA et al, 1981;MONTIEL et al, 1984;SORIMACHI and NISHIMURA, 1984) and inorganic blockers (Co, Mn, and Zn;NISHIMURA et al, 1981) of the voltage-dependent Ca channel, and thus led to the suggestion that the Ca entry pathway linked with Na efflux has pharmacological characteristics quite similar to those of the voltage-dependent Ca channel (AGUIRRE et al, 1979;SORIMACHI and NISHIMURA, 1984). However, it has recently been found that both responses to Ca re-introduction and to ouabain in the presence of Ca and Mg were greatly raise the fundamental question as to whether or not Ca entry linked with Na efflux actually occurs through the pathway distinct from the voltage-dependent Ca channel.…”
mentioning
confidence: 98%
See 2 more Smart Citations